Analisis Kecemasan Matematika dan Akurasi Pemahaman Konsep Guru Sekolah Dasar dalam Perspektif Faktor Demografis - Yohana Dwi Kristiani Sinaga; Kandida Maro Rayo (Pendidikan Matematika FKIP Universitas Mataram, 2026)
Mathematics anxiety is experienced not only by students but also by elementary school teachers and may affect instructional quality, particularly conceptual understanding accuracy. This study aimed to (1) identify teachers’ levels of mathematics anxiety, (2) examine factors associated with mathematics anxiety, and (3) analyze its effect on conceptual understanding accuracy. A quantitative correlational-regression design was employed involving 85 elementary school teachers from Teacher Working Group (KKG) Cluster 1, Sintang District. Data were collected through a mathematics anxiety questionnaire and a conceptual understanding test and analyzed using descriptive statistics, t-tests, Pearson correlation, and multiple linear regression. The results showed that teachers’ mathematics anxiety was at a moderate level. Significant differences were found based on gender and grade level taught, whereas no significant relationship was found with teaching experience. Self-confidence was negatively associated with mathematics anxiety. Furthermore, mathematics anxiety had a significant negative effect on conceptual understanding accuracy after controlling for other variables. The regression model explained 35% of the variance in conceptual understanding accuracy (R² = 0.35), with mathematics anxiety emerging as a significant negative predictor (β = −0.38, p < 0.001). These findings highlight the importance of addressing teachers’ affective factors in professional development.